Teaching and learning informatization at the universities of physical culture - Filenko, L.; Ashanin, V.; Basenko, O.; Petrenko, Y. (Journal of Physical Education and Sport, 2017)
Problem Statement. The paper describes information technologies used for training students. Approach. Computer-based training and supervisory systems improve the learning process. This research shows that the quality of computer-based training programs designed for dealing with databases in physical education and sports is insufficient. Purpose. We introduce an algorithm of creating computer-based training and control programs. We have also designed an computer-based training program – Sports & Physical Education Databases. Results. The experiment involved 240 students (n = 240). We have conducted a corresponding survey and got a 10/12 estimate after assessing the computer-based training program. The peer review has showed that respondents are equal of their opinions (ρ = 0.35; p > 0.05). Our computer-based program efficiency was tested by statistical hypotheses; its positive effect was proven by the Student’s test – t = 3.12 on the back of the t=1.98 standard (p > 0.01). Conclusion. We have analyzed the prospects of applying modern information tools in training and assessing knowledge of physical culture students. We have also identified research and development tools used to create information-based learning environments, as well as a wide range of computer training programs. This paper substantiates theoretical principles of learning based on computer training technologies. We have designed a computer-based training program for the Sports & Physical Education Databases Course that allows teaching based on the information technology.
Keywords: training; physical education; sports